Housing policy in four Lincolnshire towns, 1919-1959 - Hartley, O (1969)
﻿ This thesis attempts to deal with two problems, the relation between central and local government, and who decides policy at the local level, through the medium of a study of a major local authority service, housing, as provided in four Lincolnshire towns, Cleethorpes, Grimsby, Lincoln, and Scunthorpe, between 1919 and 1959. The problem of the relationship between central aad local government is that there are two traditions regarding the purpose of local government, giving different answers to the problem of who should prevail when central aad local government conflict on policy. One tradition sees local authorities as an administrative device for the provision of national services at a local level. The other tradition sees local authorities as independent bodies with their ovn rights and duties. According to the first view, local authorities should not have any independent policies; while, according to the second, they should, and be prepared to settle differences with central government only by negotiation between equals. Both traditions continue though to the present, but there is no clear answer as to which does, or should, prevail. Some reasons for the persistance of the confusions can be offered, but the situation seems inherently liable to open conflict. However, though policy views do differ, public conflict is very rare. Hence, the problem is to see how public policy conflict is avoided by central and local government. This first problem involves a study in detail of a number of individual local authorities and one local service, the four Lincolnshire authorities and housing being chosen. This case study approach leads itself easily to the study of the second problem, of who determines local policy. Within the scope of the case studies, the general problem can receive but limited answers, yet some light can be shed. The formal system of Councils, Committees, Chairmen, and Parties can be supplemented by considering outside pressures, the role of the individual Councillor and the Official - though the peculiar position of housing adds a further problem. Who amidst those elements of the local political scene makes the local decisions on housing policy? The two problems are investigated through the four town case studies, prefaced by an exposition of national housing policies 1919-1959, in which the first date marks the beginning of serious local and national involvement with housing, and the second a point of pause in the development of housing policies. The factors most emphasised about national policy are its close relation to political party interest, the rapidity and frequency of policy changes due to economic circumstances and changes in Governments, and the broad ignorance of any real facts of the situation. The effects of national policies on local polcies are traced in the case studies and distinctive local attitudes to housing policy brought out. Cleethorpes, from the first, disliked housebuilding; Grimsby disliked slum clearance; Lincoln anticipated national pressures for both housebuilding and slum clearance with schemes respectively in 1914 and 1928, and continued committed to a vigorous housebuilding policy; while Scunthorpe provides the case of an authority responding to local needs as well as national policy with great energy. In terms of who controlled local housing policy, it is concluded that in Cleethorpes, it was broadly the Committee, in Grimsby, Chairmen and Parties, and in Lincoln and Scunthorpe, a general consensus between Councils, Committees and Parties. A chapter is appended on minor local housing policies, that is, the quality of housing, the selection and allocation of tenants, and rents, but here too the emphasis is on Councils and Committees. In re-examining the problem of central-local relations in the conclusions, it is argued that the method employed by central government in controlling local authorities played a critical part in reducing the visibility of conflict on policy matters, even when conflict was vigorous. Control of policy is not achieved by the use of major weapons, like the power to act in default of a local authority, but by an indirect approach of threats and the use of powers to sanction particular local projects. This avoids public conflict and leaves obscure the battle in a fog of disputed detail. Such methods have their disadvantages. It is, firstly, biased towards curtailing rather than stimulating local activity, even though the latter is what national policy requires. Secondly, it is a control of detail in order to control policy, which means that national government is naturally overstretched and local authorities resentful. Thirdly, it faiils to alter local attitudes in any way over a long period - it fails to be educative. These disadvantages are accepted because the relationship is not entirely intolerable, it gives some advantages to participants and it is quite flexible in action. But, it is argued, the disadvantages are so great that some effort should be made to overcome them. It is proposed that a new kind of Inspectorate would overcome the disadvantages of the present system of control. The case is argued for housing first of all, and then for all local services. The Inspectorate would take the Central Department's control function by checking on local authorities performance of national policies and using publicity rather than devious controls to obtain local cooperation with national policy. Some disadvantages of such a proposal are noted and an attempt made to turn them into advantages is getting away from the problems of the present system. The problem of who decides policy at the local level is found to be answered by looking at the obvious political elements, Councils, Committees, Chairmen and Parties. Of limited importance are outside pressure groups, individual councillors and officials. The powers and limitations of these 'actors' on the local political scene are examined both in relation to housing and to other services. The stress laid in case studies on the role of the Official is found to be less than convincing and another argument, on the unimportance of local parties, is also dismissed. It is concluded that the obvious 'political' elements are the ones which determine local policies, though it is noted that the technical state of a local service might determine to some extent the kinds of role that all local political actors can play. This emphasis on the political is reinforced by some reflections on comparing towns. The effect of different political styles is discussed, and the reasons for differences between towns in policies is considered. It is concluded that it is the differences in political elements that explain these, and it is pointed out, in final conclusion, that local councils do have choices in their situations and local politics does make a difference to what happens to a town.